Depression and homesickness among Iranian students in University Malaya / Majid Shahmohammadi - Majid , Shahmohammadi (2014)

(untitled)
Introduction: Studying abroad has become a norm and a “must do” purpose for many scholars. Over the last few years, Malaysia has become a popular destination for students from many Islamic countries including students from Iran. Many of the studies on international students are done among Asian students travelling to western countries. Objective: This is a cross-sectional study aimed to investigate the prevalence of depression and homesickness among the Iranian students in University of Malaya and to see if there are any associated factors including level of religiosity and social support. Methods: 201 Iranian students studying in University Malaya were recruited via convenience sampling, from the various faculties in the university, there was a 87% respond rate. Their socio-demographic information was collected and they were assessed using the Dundee Relocation Inventory (DRI), the Beck Depression Inventory (BDI), the Duke University Religiosity Index (DUREL) and the Multidimensional Scale of Perceived Social Support (MSPSS-E) to assess the participants’ presence of homesickness, depression, religiosity and social support respectively. The SPSS version 21was used for analyzing the data. Results: The prevalence of depression was found to be 33.8 % (n=68) among the participants. Depression was significantly associated with homesickness (OR= 7.739; 95% CI; 3.809-15.723), poor social support, (OR=0.481; 95% CI; 0.243- 0.951) and lower intrinsic religiosity (OR=0.467; 95% CI; 0.217-1.005). The prevalence of homesickness was 44.3 % (n=89) among the participants. Homesickness was significantly associated with poor social support (OR=2.031; 95% CI; 1.046- 3.944), presence of viii depression (OR=0.144; 95% CI; 0.72-0.287) and female gender (OR=2.440; 95% CI; 1.254-4.747). Conclusion: One third of Iranian students in University Malaya are suffering from depression and it is associated with being homesick, poor social support and lower intrinsic religiosity. Almost one in two Iranian students in University of Malaya are suffering from homesickness and it is associated with the female gender, being depressed and presence of poor social support. It is worthwhile noting that services for these international students will definitely help these students cope and settle down better in achieving their undertaking. Key words: homesickness, depression, religiosity, measurement, associated factors